Metodika práce s třídním kolektivem v inkluzivní třídě se zaměřením na žáky s epilepsií Metodická příručka - Fialová, Ilona (Masaryk University Press, 2020)
Title in English: Methodology of Classroom Management in Inclusive Classroom with a Focus on Pupils with Epilepsy: Methodical Manual The aim is to characterize inclusive education of pupils with epilepsy at elementary school. It focused on introduction of epilepsy as a chronic disease and it includes specifics of inclusive education of the pupils in terms of the effect of this neurological illness and the pupil´s development of the personality. It describes the process of special needs diagnostic. It provides the analysis of the supportive measures. The text contains the examples of successful practice. It includes also an analysis and interpretation of a questionnaire SDQ, Cze, which was administered at the beginning and the end of the school year at the examined inclusive classrooms and the controlled classrooms of the participating schools.